2012
DOI: 10.1080/10538712.2012.726699
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Evaluation of a Sexual Abuse Prevention Program for Taiwanese Children

Abstract: The purpose of the current study was to develop and evaluate the efficacy of a school-based child sexual abuse prevention program for Taiwanese children. Forty-six Taiwanese children age 6 to 13 were divided into one of two groups based on their school grade and then randomly assigned to a skills-based child sexual abuse prevention program who received training immediately or a waiting-list control condition who received the training after a delay. Children's self-protection skills improved regardless of age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 41 publications
1
55
0
1
Order By: Relevance
“…We asked authors of studies in which methods of sequence generation, allocation concealment, or blinding were unclear to provide additional information (see Assessment of risk of bias in included studies). We contacted corresponding authors of studies with insufficient information to allow inclusion in meta‐analyses (Harvey 1988; Saslawsky 1986 in 2007; Chen 2012; Kraizer 1991 in 2013) and studies that used cluster‐randomisation (Dake 2003; see Unit of analysis issues) via email with a request to provide additional data. In some instances, authors were able to provide data as requested, however, the majority did not respond to requests.…”
Section: Methodsmentioning
confidence: 99%
“…We asked authors of studies in which methods of sequence generation, allocation concealment, or blinding were unclear to provide additional information (see Assessment of risk of bias in included studies). We contacted corresponding authors of studies with insufficient information to allow inclusion in meta‐analyses (Harvey 1988; Saslawsky 1986 in 2007; Chen 2012; Kraizer 1991 in 2013) and studies that used cluster‐randomisation (Dake 2003; see Unit of analysis issues) via email with a request to provide additional data. In some instances, authors were able to provide data as requested, however, the majority did not respond to requests.…”
Section: Methodsmentioning
confidence: 99%
“…Ethnicity data were reported in 13 studies. Two studies reported 100% Chinese participants (Chen et al, 2012;Lee & Tang, 1998); in five studies, the predominant ethnicity reported was White or Caucasian comprising 74% to 97% of participants (Grendel, 1991;Oldfield et al, 1996;Poche et al, 1988;Snyder, 1986;Tutty, 1997); and six studies reported diverse samples in which the proportion of non-White participants ranged from 32% (Hazzard, Webb, Kleemeier, Angert, & Pohl, 1991) to 66% (Dake, Price, & Murnan, 2003). Parental socioeconomic position, religious background, and participants' school achievement data (e.g., grades) at baseline were not reported in any study.…”
Section: Participantsmentioning
confidence: 99%
“…Contents of or topics covered in the intervention programs included safety rules, body ownership, private parts, distinguishing appropriate and inappropriate touches, distinguishing types of secrets, and whom to tell. Four studies also included abduction prevention content (Chen et al, 2012;Fryer et al, 1987aFryer et al, , 1987bS. Kraizer, 1991;Poche et al, 1988).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations